A Knotless Technique for Kidney Transplantation in the Mouse - Song Rong; Alfor G. Lewis; Uta Kunter; Hermann Haller; Faikah Gueler (Journal of Transplantation)
Mouse models of kidney transplantation are important to study molecular mechanisms of organ transplant rejection as well as to develop new therapeutic strategies aimed at improving allograft survival. However, the surgical technique necessary to result in a viable allograft has traditionally proven to be complex and very demanding. Here, we introduce a new, simple, and rapid knotless technique for vessel anastomosis wherein the last stitch of the anastomosis is not tied to the short end of the upper tie as in the classical approach but is left free. This is a critical difference in that it allows the size of the anastomosis to be increased or decreased after graft reperfusion in order to avoid stenosis or bleeding, respectively. We compared the outcome of this new knotless technique (n=175) with the classical approach (n=122) in terms of local thrombosis or bleeding, time for anastomosis, and survival rates. By this modification of the suture technique, local thrombosis was significantly reduced (1.1% versus 6.6%), anastomosis time was less, and highly reproducible kidney graft survival was achieved (95% versus 84% with the classical approach). We believe that this knotless technique is easy to learn and will improve the success rates in the technically demanding model of mouse kidney transplantation.